Psychometric Adaptation and Scaling of Morphology Module of the Battery of Objective and Criterial Language (BOCL) in children ages 6, 7 and 8, of middle class Lima - Ciccia-Gabillo, Cecilia (2004)
The present study had as an objective the psychometric adaptation of the module of morphology of the battery BOCL (Battery of Objective and Criterial Language). The module, linguistically adapted, was applied to 122 students of both sexes (32 with language disabilities), of ages between 6 and 8 years, of middle class metropolitan Lima. The results showed that the adaptation scores were reliable. Thus, it was concluded that the test had construct validity (measured through the item analysis and factorial analysis) and criterion validity (studied through the groups’ comparison). Percentiles of the adapted module of Morphology are presented.